The Wisdom of I'jazu Al-Qur'an for Non-Muslims - Nurmila; Syabuddin (Penerbit Hellow Pustaka, 2025)
Miracles are instructions from Allah SWT to humans regarding the truth of His Apostles and Prophets. They are truly messengers of Allah and they only give news, convey messages from Allah SWT. Allah gives miracles to prove the truth of his prophethood and apostolate. It is usually not easy for every people to simply accept the call/preaching of the Apostles before they know the proof of the truth that he is the messenger of Allah. So miracles are very necessary so that his people can accept his call. The miracles received by the Prophet Muhammad SAW are very many, but the greatest is the Al-Qur'an Al-Karim, the last divine revelation holy book revealed to his Messenger as a guide and guide to life for all mankind in the world, a holy book whose purity will be kept by Allah until the end of time, The contents of the Al-Qur'an Al-Karim include, for news of the unseen (The occurrence of war between the Roman Empire and the Persian Empire and victory on the Roman side), historical information (The story of the Prophet Adam, the Prophet Noah and others are events thousands of years before the Prophet Muhammad SAW), science (The Qur'an suggests that